“Clickable” Nanoparticles for Targeted Imaging - Eric Yi Sun; Lee Josephson; Ralph Weissleder (Molecular Imaging)
Nanomaterials functionalized with targeting ligands are increasingly recognized as useful materials for molecular imaging and drug delivery. Here we describe the development and validation of azide–alkyne reactions (“click chemistry”) for the rapid, site-specific modification of nanoparticles with small molecules. The facile preparation of stable nanoparticles bearing azido or alkyne groups capable of reaction with their corresponding counterpart functionalized small molecules is demonstrated. The Cu(I)-catalyzed cycloaddition of azides and alkynes is shown to be a highly efficient and selective method for point functionalization of magnetic nanoparticles. Derivatized nanoparticles bearing biotin, fluorochrome, or steroid moieties are stable for several months. Nanoparticle click chemistry will be useful for other nanomaterials, design of novel sensors, and drug delivery vehicles.